EFFECTS OF CORONAVIRUS 2019 (COVID-19) IN THE LEARNING PROCESSES OF UNIVERSITIES IN INDONESIA - Dewi Alima Nostalia Suseno; Dewi Nurmalita Suseno; Moch Saad; Adi Suseno (Erudio Journal of Educational Innovation, 2020)
Background: The global pandemic that has affected many parties, digital transformation in increasing connectivity, the speed of change, the modern world, and improving education around the world is one solution that can be done. Purpose: The purpose of this study is to describe the opinions of Indonesian students in distance learning during the pandemic coronavirus 2019 (COVID-19). Methods: The method used is the technique of accidental sampling and regression analysis with SPSS software ver.16. Results: 76.2% of distance learning with practicum is difficult to understand, 31.7% experienced boredom, 82.5% often experienced difficulties with signal difficulty, 47.6% had difficulties when using media, 60.3% more time-consuming learning activities, 69.8% more spend money. Conclusion: There are significant differences between X1-X10 and Y1 and Y2 as well as the influence during the (COVID-19) (X) on changes in learning before and after (COVID-19) (Y2).